Borders of Belief Religious Nationalism and the Formation of Identity in Ireland and Turkey - Goalwin, Gregory J. (New Brunswick, NJ Rutgers University Press, 2022)
Religion and nationalism are two of the most powerful forces in the world. And as powerful as they are separately, humans throughout history have fused religious beliefs and nationalist politics to develop religious nationalism, which uses religious identity to define membership in the national community. But why and how have modern nationalists built religious identity as the foundational signifier of national identity in what sociologists have predicted would be a more secular world? This book takes two cases - nationalism in both Ireland and Turkey in the 20th century - as a foundation to advance a new theory of religious nationalism. By comparing cases, Goalwin emphasizes how modern political actors deploy religious identity as a boundary that differentiates national groups This theory argues that religious nationalism is not a knee-jerk reaction to secular modernization, but a powerful movement developed as a tool that forges new and independent national identities
ABOUT THE AUTHOR
In English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Church and state -- Ireland; Islam and state -- Turkey; Nationalism -- Religious aspects -- Catholic Church; Nationalism -- Religious aspects -- Islam; Nationalism -- Ireland -- Religious aspects; Nationalism -- Turkey -- Religious aspects; RELIGION / General; belief, religion, nationalism, nation building, national identity, religious identity, community, Turkey, Ireland, 20th century, twentieth century, secular, secularism, independence, modern, modernization, politics, identity, Catholicism, Catholic Church, Islam